A GIS BASED EVALUATION OF LAND USE CHANGES AND ECOLOGICAL CONNECTIVITY INDEX - Poppy Indrayani; Yasuhiro Mitani; Ibrahim Djamaluddin; Hiro Ikemi (Department of Urban and Regional Planning, Diponegoro University, 2017)
Recently, the Makassar region is a significant land use planning and management issue, and has many impacts on the ecological function and structure landscape. With the development and infrastructure initiatives mostly around the urban centers, the urbanization and sprawl would impact the environment and the natural resources. Therefore, environmental management and careful strategic spatial planning in landscape ecological network is crucial when aiming for sustainable development. In this paper, the impacts of land use changes from 1997 to 2012 on the landscape ecological connectivity in the Makassar region were evaluated using Geographic Information System (GIS). The resulted GIS analysis clearly showed that land use changes occurring in the Makassar region have caused profound changes in landscape pattern. The spatial model had a predictive capability allowing the quantitative assessment and comparison of the impacts resulting from different land use on the ecological connectivity index. The results had an effective performance in identifying the vital ecological areas and connectivity prior to development plan in areas.